2017
DOI: 10.1016/j.bbrc.2017.06.195
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of calcium release from the endoplasmic reticulum by the serine hydrolase ABHD2

Abstract: The serine hydrolase inhibitors pyrrophenone and KT195 inhibit cell death induced by A23187 and H2O2 by blocking the release of calcium from the endoplasmic reticulum and mitochondrial calcium uptake. The effect of pyrrophenone and KT195 on these processes is not due to inhibition of their known targets, cytosolic phospholipase A2 and α/β-hydrolase domain-containing (ABHD) 6, respectively, but represent off-target effects. To identify targets of KT195, fibroblasts were treated with KT195-alkyne to covalently l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…A previous study demonstrated that the down-regulation of ABHD4 suppresses the OVCAR3 ovarian cancer cells (27). ABHD2 knockdown accompanied by shRNA could induce the apoptosis of broblasts with A23187 (28). Moreover, ABHD5 as one of α/β-hydrolase members, and the protein-related factor of triacylglycerol hydrolase activity stimulated by ATGL is consider as the suppressor factor in colorectal cancer (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that the down-regulation of ABHD4 suppresses the OVCAR3 ovarian cancer cells (27). ABHD2 knockdown accompanied by shRNA could induce the apoptosis of broblasts with A23187 (28). Moreover, ABHD5 as one of α/β-hydrolase members, and the protein-related factor of triacylglycerol hydrolase activity stimulated by ATGL is consider as the suppressor factor in colorectal cancer (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…The data regarding the number of exons were obtained from BioGPS, and the data regarding the relatively high expression in normal human tissues were primarily obtained from the BioGPS portal and the reported references. protein name molecular weight (kDa) aliases gene location in humans number of exons relatively high expression in normal human tissues (BioGPS) related function or role in disease ABHD1 45 LABH1 2p23.3 9 testis, sperm saphenous related to oxidative stress in mouse and rat models [ 29 32 ]; expression downregulation is driven by hepatic steatosis and insulin resistance induced by Notch signalling [ 33 ] ABHD2 48 HS1–2, LABH2, PHPS1–2 15q26.1 16 prostate, lung, NK cells, whole blood a glyceridase and ester hydrolase cleaving 2AG and leading to sperm hyperactivation in a progesterone-dependent manner [ 34 36 ]; an androgen-regulated gene promoting prostate cancer growth and resistance to chemotherapy [ 37 ]; essential for the reproduction of HBV [ 38 , 39 ]; involved in calcium transfer from the endoplasmic reticulum to mitochondria [ 40 ] and chronic obstructive pulmonary disease (COPD) in a Chinese Han population [ 41 ]; associated with anoikis resistance in ovarian cancer [ 7 ] and possibly associated with tumorigenesis in hepatocytes, stomach cells and colon cells [ 42 , 43 ] ABHD3 46 LABH3 18q11.2 12 colon, small intestine, whole blood a brain serine hydrolase related to the activation of the endocannabinoid system [ 44 ]; a lipase playing the role of...…”
Section: Research Progress Related To the Abhd Family Membersmentioning
confidence: 99%
“…rsob.royalsocietypublishing.org Open Biol. 8: 180017 [34 -36]; an androgenregulated gene promoting prostate cancer growth and resistance to chemotherapy [37]; essential for the reproduction of HBV [38,39]; involved in calcium transfer from the endoplasmic reticulum to mitochondria [40] and chronic obstructive pulmonary disease (COPD) in a Chinese Han population [41]; associated with anoikis resistance in ovarian cancer [7] and possibly associated with tumorigenesis in hepatocytes, stomach cells and colon cells [42,43] ABHD3 46 LABH3 18q11.2 12 colon, small intestine, whole blood a brain serine hydrolase related to the activation of the endocannabinoid system [44]; a lipase playing the role of a physiological regulator in the metabolism of medium-chain phospholipids [45]; possibly influences innate immunity by transcription factor T-bet [46] ABHD4 39 ABH4 14q11.2 8 adipocyte, testis functions in N-Acyl ethanolamine synthesis as a (lyso) N-acyl phosphatidylethanolamine-selective lipase [47,48]; a novel regulator of anoikis resistance [49] (Continued.) rsob.royalsocietypublishing.org Open Biol.…”
Section: A Regulator or Marker Of Certain Cancersmentioning
confidence: 99%
“…ABHD2 and NUDT21 were selected as candidate targets of miR-4454 based on information from online databases. Yun et al [21] described a novel mechanism by which the serine hydrolase ABHD2 regulates calcium transfer from the endoplasmic reticulum to the mitochondria to affect cell death (anoikis) resistance, which is related to malignant phenotypes and is a hallmark of cancer. Yamanoi et al [22] showed that down-regulation of ABHD2 could promote a malignant phenotype and was associated with a poor prognosis for women with serous ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%